Review: Radicalizing Enactivism: Basic Minds without content - Satne, Glenda Lucila (2013)
Until very recently, the field of cognitive science was (almost) in complete agreement in characterizing the mind as a computational mechanism dealing with brain-based representations to produce actions. Accordingly, cognition was defined as always involving represented information and neurally-based computational processes operating on it. In the last decade or so, an alternative to the representational brain paradigm started to emerge, especially from those who defend a conception of human minds as embodied and embedded in physical and social environments (systems in which brain, bodies, and the world are thought to form an indivisible whole). Is this emerging paradigm—enactivism—a genuine alternative to the representational–computational model of the mind or just an extension of it? Answering this question is the...